The Treatment Outcomes of Patients with Cervical Esophageal Carcinoma Undergoing Definitive Chemoradiotherapy: A Multi-Institutional Analysis TROD 01-005 - Guler, O. C.; Oymak, E.; Yazici, G.; Akagunduz, O. Ozkaya; Cetinayak, O.; Erpolat, P.; Aksoy, A.; Duzova, M.; Yildirim, B. Akkus; Kurt, M.; Canyilmaz, E.; Akyurek, S.; et al. (ELSEVIER SCIENCE INC, 2022)
Annual Meeting of the American-Society-for-Radiation-Oncology (ASTRO), ELECTR NETWORK, OCT 23-26, 2022